Current Understanding of IL-37 in Human Health and Disease - Su, Zhangci; Tao, Xiaoan (Frontiers in Immunology, 2021)
IL-37 is a recently discovered cytokine in the IL-1 family exerting broad protective effects on inflammatory diseases, autoimmune diseases, and cancer. Immune and non-immune cells produce the IL-37 precursor upon pro-inflammatory stimuli. Intracellularly, caspase-1 cleaves and activates IL-37, and its mature form binds to Smad3; this complex translocates into the nucleus where it suppresses cytokine production, consequently reducing inflammation. Extracellularly, IL-37 forms a complex with IL-18Rα and IL-1R8 (formerly TIR8 or SIGIRR) that transduces anti-inflammatory signals by the suppression of NF-κB and MAPK and the activation of Mer-PTEN-DOK pathways. During inflammation, IL-37 suppresses the expression of several pro-inflammatory cytokine in favor to the expression of the anti-inflammatory ones by the regulation of macrophage polarization, lipid metabolism, inflammasome function, TSLP synthesis and miRNAs function. Moreover, IL-37 not only regulates the innate and acquired immunity, but also improves aging-associated immunosenescence. Furthermore, IL-37 exerts an inhibitory effect on tumor angiogenesis and metastasis, and progression. Finally, IL-37 may have a potential ability to reduce excessive inflammation since it is aberrantly expressed in patients with inflammatory diseases, autoimmune diseases, and cancer, thus, it may be used as a marker for different types of diseases. Therefore, this review provides an updated view of the role of IL-37 in human health and disease, and discusses the potential of IL-37 as a therapeutic target and biomarker in inflammatory diseases, autoimmune diseases, and cancer.